Measuring for change/Mobile Creches - Chavi Vohra; Chavi Vohra; Chavi Vohra; Chavi Vohra; Minal Shah; Minal Shah; Minal Shah; Minal Shah; Atishi Mishra; Atishi Mishra; Ankita Gupta (Frontiers Media S.A., 2024)
IntroductionResearch spanning decades across fields such as psychology, education, and neuroscience consistently highlights the crucial role of social-emotional skills in various aspects of personal, academic, and professional development (1-3). The fact that UNESCO recognises social-emotional learning (SEL) as essential not just for meeting its educational objectives but also for accomplishing the Sustainable Development Goals highlights the crucial role robust social-emotional development plays in establishing sustainable societies. Whilst various studies highlight the importance of SEL, there is limited attention on how organizations can contribute to building such development by consciously including SEL in their work practice.Process/methodsOur case study presents the process of integrating SEL into organizational practice over a period of 9 months. The selected constructs of SEL were determined by the organisation's needs and values. The Measurement for Change approach was used to frame and implement the intervention, with interactive discussions being the key methodology. Data were collected via surveys, reflective sharing, and observations.ResultsA shift in the selected constructs of SEL was recorded, with data highlighting individual differences.ConclusionThe process of co-design and continual reflective practice was key to achieving change within the subset of the organisation rather than the specific content of the materials used.